ChemInform Abstract: Crystal Structure of Mg0.39(2)NiSn1.61(2) and Mg2.61(2)Ni4Sn3.39(2) Featuring Mg/Sn Atom Networks with Different Connections of Ni@(Mg/Sn)8 Coordination Polyhedra. Issue 19 (May 2015) - Siggelkow, Lisa; Hlukhyy, Viktor; Faessler, Thomas F.
Abstract: Mg0.39 NiSn1.61 (I) and Mg2.61 Ni4 Sn3.39 (II) are prepared by melting of the elements (sealed Ta ampoules, 700 °C, 2 weeks).